Gestao florestal na Amazonia brasileira: avanços e obstaculos em um sistema federalista - Toni, F. (CIFOR and IDRC, 2006)
Since the 1990’s many Latin American countries have been decentralizing administrative, fiscal and political authority from national to state and municipal governments. This process has often included the governance of natural resources, particularly of forests. In the study “Forestry decentralization in Latin America: looking to the future”, CIFOR analyses forestry decentralization policies and, in particular, their effects on forest-dependent groups. This book presents the results of the case study in the Brazilian Amazon, where state and municipal governments have begun to play more active roles in managing forest resources. Among other things, the author finds that indigenous groups are in conflict with many other actors in the region, and that their political power at the local level is minimal. He thus concludes that presence of the national administration is crucial for protecting the interests of indigenous groups. The author provides a range of data on land occupation and the forest sector in the region, and discusses the institutional and legal framework of forest management to examine the constraints and opportunities of forestry decentralization. He also presents examples of decentralized forest governance at the state level in Acre, Amazonas and Pará, as well as a variety of municipal level experiences. The book ends with a brief discussion of priority issues for future research that would help promote effective and equitable forestry decentralization in the Brazilian Amazon.